Concurrent Liver Hodgkin Lymphoma and Nodular Regenerative Hyperplasia on an Explanted Liver with Clinical Diagnosis of Alcoholic Cirrhosis at University Hospital Fundación Santa Fe de Bogotá - R. López; L. Barrera; A. Vera; R. Andrade (Case Reports in Pathology)
Liver involvement by Hodgkin lymphoma (HL) is well documented. However, secondary liver failure to this neoplastic process is rare and usually presents late in the course of the disease. We present a case of a HL associated with nodular regenerative hyperplasia (NRH) diagnosed on an explanted liver from a 53-year-old patient with clinical diagnosis of alcoholic cirrhosis. Hematoxylin and eosin stain (H&E) showed abnormal liver architecture with hepatocytes nodules highlighted by reticulin stain with absent fibrosis on the trichrome stain. The portal spaces had diffuse infiltration by Reed-Sternberg cells positive for CD15, CD30, and latent membrane protein (LMP) on immunohistochemical studies. The patient also had a concurrent hilar lymph node biopsy that also showed HL involvement. Liver failure as the initial presentation of Hodgkin’ lymphoma is rare. We believe that more research about the utility of performing liver biopsies in patients candidates for transplantation with noncirrhotic hepatic failure is needed in order to establish the etiology and the optimal treatment.